Smartphone-based medical diagnostics with microfluidic devices - Kim, Dong Woo; Jeong, Kwan Young; Yoon, Hyun C. (Smartphone Based Medical Diagnostics, 2019)
We have recently witnessed substantial advances in the microfluidic lab chip technology and its development toward stand-alone diagnostic devices. These efforts have been translated into commercialization-ready prototypes by incorporating smartphones and wearable devices as signal transducing and data processing equipment. Such integrated systems provide numerous advantages, including low-cost manufacturing, facile fabrication, and intuitive data processing. All the biosensing procedures, including signal generation, transducing, data processing, and displaying results, can be efficiently operated in the stand-alone device. Recent accomplishments in these efforts are reviewed and summarized.
Keywords: Microfluidics; Point-of-care testing; Smartphone diagnosis